Association between vitamin D deficiency and risk of venous thromboembolism: a matched cohort study of 139,690 patients - Hung, Kuo-Chuan; Chang, Li-Chen; Hsu, Chih-Wei; Wu, Jheng-Yan; Yu, Chia-Hung; Ho, Chun-Ning; Yew, Ming; Chen, I-Wen (Frontiers in Nutrition, 2025)
BackgroundVitamin D deficiency (VDD) may contribute to venous thromboembolism (VTE) through effects on coagulation and endothelial function, but existing studies show inconsistent results. We investigated the association between VDD and VTE risk using a large matched cohort design.MethodsWe conducted a retrospective matched cohort study using the TriNetX database, including patients aged ≥45 years with serum 25-hydroxyvitamin D (25(OH)D) measurements between 2010 and 2023. VDD was defined as serum 25(OH)D < 20 ng/mL, while controls had levels ≥30 ng/mL. After 1:1 propensity score matching, the final cohort comprised 69,845 patients in each group. Primary outcomes were deep vein thrombosis (DVT) and pulmonary embolism (PE) occurring 3–12 months after the index date. Secondary outcomes included all-cause mortality and intensive care unit (ICU) admission.ResultsDuring one-year follow-up, VDD was significantly associated with increased risk of DVT (Hazard ratio [HR] 1.62, 95% confidence interval [CI]: 1.37–1.92; p < 0.001) and PE (HR 1.62, 95% CI: 1.34–1.96; p < 0.001) compared to controls. The association persisted over 2 years with modest attenuation (DVT: HR 1.49; PE: HR 1.61). A dose–response relationship was observed, with vitamin D insufficiency (20–30 ng/mL) showing intermediate risk levels (DVT: HR 1.36; PE: HR 1.43). VDD was also associated with higher mortality (HR 2.20, 95% CI: 1.99–2.43) and ICU admission risks (HR 1.47, 95% CI: 1.33–1.62). Subgroup analyses revealed consistent associations across demographic groups, with diabetes mellitus significantly modifying the DVT association.ConclusionVitamin D deficiency is independently associated with increased VTE risk in a dose-dependent manner, with effects extending to mortality and healthcare utilization. These findings support vitamin D optimization for VTE prevention, though randomized trials are needed to establish causality.